The effects of collaborative mobile learning approach on academic performance: The mediating role of social interaction, and learning motivation - Tiantian, Yang; Razali, Abu Bakar; Zulkifli, Nurul N.; J. Jeyaraj, Joanna (Duzce University, Faculty of Education, 2024)
Recognizing the roles that English vocabulary, social interaction, academic performance, and learning motivation play in language learning can be useful in chiefly enhancing EFL language acquisition. This research explores the challenges that the pre-college EFL students encounter while expanding their word learning knowledge, communicating in the social setting, academically performing, and maintaining learning motivation. To address these challenges, the study explores how a collaborative mobile learning approach can be used to address the challenges and improve language learning for pre-college EFL students. A total of 326 students participated in the study. Data were collected by using a self-developed survey questionnaire with predefined questions to avoid inconsistency in responses. Using the PLS-SEM approach on the collected data, the study identified several significant relationships among the accepted collaborative mobile learning approach, social interaction, motivation to learn English, and the outcome knowledge of new English vocabulary. However, the experiment established that motivation to learn predicted the relationship between mobile collaborative learning and increases in effective vocabulary scores in English as well as academic performance. These significant findings show the essence of creating a spirit of collaboration and a learning environment that focuses on mobile learning, students, and their motivation for effective learning of EFL language goals among pre-college students. As such, this study has important implications for teaching and learning processes in general and valuable implications for the teaching and learning of EFL in particular, offering practical suggestions as to how the educational process could be improved for learners, educators, educational administrations, and policymakers. © 2024, Duzce University, Faculty of Education. All rights reserved.